2011
DOI: 10.1007/s10565-011-9181-y
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum exposure alters behavioral parameters and increases acetylcholinesterase activity in zebrafish (Danio rerio) brain

Abstract: Aluminum is a metal that is known to impact fish species. The zebrafish has been used as an attractive model for toxicology and behavioral studies, being considered a model to study environmental exposures and human pathologies. In the present study, we have investigated the effect of aluminum exposure on brain acetylcholinesterase activity and behavioral parameters in zebrafish. In vivo exposure of zebrafish to 50 μg/L AlCl(3) for 96 h at pH 5.8 significantly increased (36%) acetylthiocholine hydrolysis in ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 38 publications
3
34
0
1
Order By: Relevance
“…The decrease of locomotor activity after a short treatment with aluminum have also been observed in vertebrates (Abdel‐Aal et al ., ; Senger et al ., ) and seems to be correlated with the brain damage, especially in the cholinergic system. The analysis of locomotor activity is a common method to examine aging (Rakshit et al ., ) and neurotoxic effects of various substances including aluminum (Senger et al ., ). In this study we observed changes in behavior but did not test biochemical changes in the fruit fly brain.…”
Section: Discussionmentioning
confidence: 89%
“…The decrease of locomotor activity after a short treatment with aluminum have also been observed in vertebrates (Abdel‐Aal et al ., ; Senger et al ., ) and seems to be correlated with the brain damage, especially in the cholinergic system. The analysis of locomotor activity is a common method to examine aging (Rakshit et al ., ) and neurotoxic effects of various substances including aluminum (Senger et al ., ). In this study we observed changes in behavior but did not test biochemical changes in the fruit fly brain.…”
Section: Discussionmentioning
confidence: 89%
“…Because diazepam exerts its effects by binding to neuronal GABA receptors, there is also the potential that chlorpyrifos may modify GABAergic neurons, or GABA levels. Overall, the observed behavioral defects following chlorpyrifos exposure are concerning, especially since long-term behavioral changes induced by fetal exposure to stress, drugs, and environmental toxicants, including chlorpyrifos, have been documented in other species, including humans (Beer et al, 2004; Berkowitz et al, 2004; Dufour-Rainfray et al, 2011; Lazinski et al, 2008; Senger et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…It is well known that apoptosis underlies the neurotoxic effects of various compounds. Moreover, zebrafish brain AChE activation has also been demonstrated as a consequence of exposure to known neurotoxic compounds, including aluminum [20] and ethanol [21] and to the cyanobacterial toxin microcystin-LR [50]. …”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of brain AChE activity of aquatic species by toxic substances such as methanol [16], heavy metals mercury, and lead [17], neurotoxins [18], and organochlorine pesticide endosulfan [19] also has been well established. On the other hand, AChE activation has also been demonstrated as a consequence of exposure to neurotoxic compounds such as aluminum [20] and ethanol [21]. …”
Section: Introductionmentioning
confidence: 99%